1991
DOI: 10.1139/f91-187
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Wetlands of Three Canadian Great Lakes: Inventory, Current Conservation Initiatives, and Patterns of Variation

Abstract: The decline of wetlands, including those in the Great Lakes coastal zone, prompted the Government of Ontario to initiate steps towards a wetland management policy in 1981. Wetland inventory and evaluation in southern Ontario began in 1983. To date, 1982 wetlands have been evaluated totalling 390 000 ha. These include 160 coastal wetlands, 64 of these on Lake Ontario and the remainder on the other Great Lakes and connecting channels. Current wetland conservation initiatives are outlined including the Wetlands P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The macrophyte community also reflects the physical conditions in a wetland (Lougheed et al, 2001;Croft and Chow-Fraser, 2007;Trebitz et al, 2009), as well as climatic and geological factors (Smith et al, 1991;Lougheed et al, 2001;De Catanzaro et al, 2009). In addition, morphology of the wetland will influence the type of aquatic vegetation, as high exposure and fetch can prevent establishment of many macrophyte species at a site, both directly through disturbance by wave action and burial by sediment, and indirectly through slow organic soil accretion (Keddy, 1983(Keddy, , 1985Randall et al, 1996;Wei, 2007;Cvetkovic, 2008;Trebitz et al, 2009).…”
Section: Tablementioning
confidence: 99%
“…The macrophyte community also reflects the physical conditions in a wetland (Lougheed et al, 2001;Croft and Chow-Fraser, 2007;Trebitz et al, 2009), as well as climatic and geological factors (Smith et al, 1991;Lougheed et al, 2001;De Catanzaro et al, 2009). In addition, morphology of the wetland will influence the type of aquatic vegetation, as high exposure and fetch can prevent establishment of many macrophyte species at a site, both directly through disturbance by wave action and burial by sediment, and indirectly through slow organic soil accretion (Keddy, 1983(Keddy, , 1985Randall et al, 1996;Wei, 2007;Cvetkovic, 2008;Trebitz et al, 2009).…”
Section: Tablementioning
confidence: 99%
“…However, the index development largely ignored geographic location (i.e., latitude) and degree of development in the watershed, which loaded significantly on the second axis of the pCCA. Other authors have also shown that the wetland environments in the upper and lower lakes are unique, due largely to differences in climate, geology, and exposure (Smith et al 1991), and that this has important consequences for the macrophyte community (Minc 1997;Lougheed et al 2001). In fact, both the abundance and species richness of rotifers and cladocerans varied inversely with latitude (r 2 ϭ 0.05; P Ͻ 0.0001), with 57 of the 138 zooplankton taxa identified in this study absent from the upper lakes (see the Appendix).…”
Section: Discussionmentioning
confidence: 99%
“…Oriented as they are between the granitic-based boreal ecosystem of northem North America and the sedimentary bedrock and glacial deposits of the midwestern U. S., the Great Lakes encompass a wide range of environments for wetland development (Smith et al 1991). Lake Superior is less alkaline and less saline (lower specific conductance) than the others, while Lake Erie has most available phosphorus and highest turbidity ( Table 1).…”
Section: Other Site-specific Physical Factorsmentioning
confidence: 99%